Nanoporous Silica-Dye Microspheres for Enhanced Colorimetric Detection of Cyclohexanone - Zheng Li (Chemosensors, 2018)
Forensic detection of non-volatile nitro explosives poses a difficult analytical challenge. A colorimetric sensor comprising of ultrasonically prepared silica-dye microspheres was developed for the sensitive gas detection of cyclohexanone, a volatile marker of explosives 1,3,5-trinitro-1,3,5-triazinane (RDX) and 1,3,5,7-tetranitro-1,3,5,7-tetrazocane (HMX). The silica-dye composites were synthesized from the hydrolysis of ultrasonically sprayed organosiloxanes under mild heating conditions (150 °C), which yielded microspherical, nanoporous structures with high surface area (~300 m2/g) for gas exposure. The sensor inks were deposited on cellulose paper and given sensitive colorimetric responses to trace the amount of cyclohexanone vapors even at sub-ppm levels, with a detection limit down to ~150 ppb. The sensor showed high chemical specificity towards cyclohexanone against humidity and other classes of common solvents, including ethanol, acetonitrile, ether, ethyl acetate, and ammonia. Paper-based colorimetric sensors with hierarchical nanostructures could represent an alternative sensing material for practical applications in the detection of explosives.